Honneth e o mercado brasileiro de consumo como instituição de reconhecimento - Carlos Freitas (Ciências Sociais Unisinos)
This text presents a sociological analysis of the theme of consumption as a sphere of “intersubjective freedom”. Informed by the “theory of justice as an analysis of society” as articulated by Axel Honneth, the author clarifies the extent to which the sphere of consumption, understood as a “subsystem” of the economic market, may present itself (in its practices) as the realization of values socially institutionalized. For this, in the first moment, a systematic review of the literature is made that articulates the nexus between economy and morality, in the sphere of the consumption mediated by the market, in particular in the most current studies of Axel Honneth. Next, an examination of empirical situations of forms of intersubjective recognition in the sphere of market-mediated consumption is made. We highlight the recent visibility and affirmation of sexual and ethnic diversity in the advertising industry of the Brazilian consumer market. The empirical analysis relied exclusively on textual and audiovisual content linked to selected materials from advertising campaigns. In the end, it is desired to demonstrate the potential normative advances and controversies that surround the Brazilian market of consumer goods.